PENINGKATAN KEMAMPUAN MENULIS TEKS NEGOSIASI TIPE ROUND TABLE KELAS X SMAN 2 SUNGAI KAKAP - Mangguali, Yostina Lilis; Priyadi, A. Totok; Saman, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
ABSTRACTThis is a qualitative descriptive research which aims to: (1) describe the planning of round table cooperative learning model to the X MIA students of SMA N 2 Sungai Kakap; (2) describe the use of round table cooperative learning model in negotiation text writing to the X MIA students of SMA N 2 Sungai Kakap; (3) describe the planning, use, and result of the class action research in using round table cooperative learning model in negotiation text writing to the X MIA 1 students of SMA N 2 Sungai Kakap. The subjects in this research were the teacher and students of X MIA students of SMA N 2 Sungai Kakap Kubu Raya regency. The methods used in collecting the data were documentation, observation, and interview. The data was analyzed with descriptive method. The results are: (1) round table cooperative learning model planning made by the teacher in form of RPP is in accordance with 2013 curriculum component; (2) the use of round table cooperative learning done by the teacher is in accordance with syntax of round table cooperative learning model; (3) the learning result in the use of round table cooperative learning model in negotiation text writing to the students.Â Keywords: Round Table Cooperative Model, Negotiation Text